PROMOTING AN INCLUSIVE ECONOMY: THE RELEVANCE OF SUSTAINABLE DEVELOPMENT AND ISLAMICITY PROSPERITY INDEX - Ismail, Nor Hazila; Mohd Rasid, Mohamed Eskandar Shah (Journal of Islamic Monetary Economics and Finance, 2022)
Inequalities and social exclusion are the consequences of imbalanced economic growth, prompting the World Bank to establish new targets for eradicating extreme poverty and promoting shared prosperity. Surprisingly, the contemporary solution methods are consistent with Shari'ah's objectives. Stressing the importance of balanced growth, this study aims to quantify prosperity sharing in 28 developed and 14 developing nations by reshaping the notion of sustainable development from an Islamic perspective. The study examins four pillars of prosperity namely Faradh (social responsibility), Shura (social participation), Al Adl Wal Ihsan (social equilibrium) and Ummah (social cohesion) to capture the essence of prosperity sharing. It begins with a thorough literature review as the basis for designing and developing the dimensions and indicators, followed by an adequacy test of the indicators using Principal Component Analysis (PCA). Then, the study employs panel data regression analysis to identify the determinants that have a significant impact on the shared prosperity indicator (s). The results show that all of the pillars (Faradh, Shura, Al Adl Wal Ihsan, and Ummah) have a significant outcome, confirming that the strength of the association between the variables is strong and adequate as proxies for each pillar. Finally, an Islamicity Prosperity Index is developed, which is a multidimensional index (iPI) to measure prosperity sharing in developed and developing countries.